GEOLOGY AND ANALYSIS OF URBAN ENVIRONMENTAL GEOLOGY SPECIAL ECONOMIC AREA OF MANDALIKA AND ITS SURROUNDINGS, PUJUT DISTRICT, CENTRAL LOMBOK REGENCY, WEST NUSA TENGGARA PROVINCE - RAMADHAN UMAR , ISMAR
Kawasan Ekonomi Khusus (KEK) Mandalika was designated as a tourism area through PP number 52 of 2014. KEK Mandalika as one of four from ten “New Bali” tourist destinations which are focused on development by the government. Development plan of Kawasan Ekonomi Khusus requires environmental geology analysis as an initial stage. The research area is located at coordinates 424000- 435000 mT and 9009500 - 9019000 mU (UTM WGS 1984 Zone 50S). The research covers area is 50.78 km2. The method used are literature studies, field mapping, petrographic and micropaleontological laboratory analysis, and urban environmental geology analysis. The data were processed and digitized to produce urban environmental geology parameter map then overlay by the weight obtained from the AHP (Analytical Hierarchy Process) calculation. The geomorphology of the study area consists of Coastal Plain Units, Alluvial Plain Unit, Lava Flow Hills Unit, Fault Zone Hills Unit, Raised Karst Hills Units. The geomorphic process of the study area is mature to old. The geology of the study area consists of Andesite Unit, Sandstone-Breccia Unit, Basalt Unit, Tuff Unit, Dacite Unit, Calcarenite Unit, and Alluvial and Coastal Deposition Unit. The urban environmental geology analysis shows that the recommended zoned KEK Mandalika for city development is the Free Zone (5.6%), Fairly Free Zone (17.9%), and Rather Free Zone (24.3%). The non-recommended zone is the Less Free Zone (2.9%) and the Unrestricted Zone (49.3%).